Laminate design for a tapered FRP structure with ply drop-off based on yielding of resin pockets. (1st December 2020) - Obata, Sae; Takahashi, Kosuke; Inaba, Kazuaki
Abstract: In this study, a design procedure is proposed for a tapered FRP laminate with ply drop-offs to suppress the damage initiation. A stress index, based on the von Mises yield criteria, is defined and applied to the resin pockets formed adjacent to cut plies. First, finite element (FE) analysis of a three-ply tapered laminate consisting of a cover layer, a dropped layer, and a base layer is conducted to relate the fiber directions with the stresses caused by a ply drop-off. Using the stress values obtained from the FE analysis, a tapered quasi-isotropic laminate with a thickness decreasing from 16 to 8 layers is appropriately designed by minimizing the overall stress indexes in ply-dropped locations. The observation of the specimen manufactured by autoclave molding reveals that the resin pockets can be effectively eliminated by the appropriate design. The tensile tests also verify the higher load capacity.